Leukotoxin production by Fusobacterium necrophorum biotypes - Z. Tan; M. M. Chengappa; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1990)
Fusobacterium necrophorum biotypes A and B were grown anaerobically to detect their leukotoxin production. Both biotypes exerted the highest leukotoxic effect on bovine leukocytes in the late logarithmic and early stationary growth places. Biotype A produced more leukotoxin than biotype B throughout all phases of bacterial growth. Results are consistent with the findings that biotype A is more virulent than biotype B.
Keywords: Cattlemen' s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Leukotoxin; F. necrophorum; Biotype; Growth phase; Liver abscesses